2008
DOI: 10.1152/ajpheart.91469.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modest maternal caffeine exposure affects developing embryonic cardiovascular function and growth

Abstract: Momoi N, Tinney JP, Liu LJ, Elshershari H, Hoffmann PJ, Ralphe JC, Keller BB, Tobita K. Modest maternal caffeine exposure affects developing embryonic cardiovascular function and growth. Am J Physiol Heart Circ Physiol 294: H2248-H2256, 2008. First published March 21, 2008 doi:10.1152/ajpheart.91469.2007.-Caffeine consumption during pregnancy is reported to increase the risk of in utero growth restriction and spontaneous abortion. In the present study, we tested the hypothesis that modest maternal caffeine ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 51 publications
4
57
1
2
Order By: Relevance
“…Both xenobiotics have been comprehensively studied as risk factors during pregnancy. Among many other observations in the literature, it is known that caffeine intake increases the risk of early spontaneous abortion among nonsmoking women (Cnattingius et al, 2000), whereas modest maternal caffeine exposure may impair fetal cardiovascular function and growth (Momoi et al, 2008) and also promotes long-lasting behavioral changes in mouse offspring (Björklund et al, 2008). Nicotine exposure during pregnancy has also been related to a variety of harmful effects, including, among many others, intrauterine growth retardation (Einarson and Riordan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Both xenobiotics have been comprehensively studied as risk factors during pregnancy. Among many other observations in the literature, it is known that caffeine intake increases the risk of early spontaneous abortion among nonsmoking women (Cnattingius et al, 2000), whereas modest maternal caffeine exposure may impair fetal cardiovascular function and growth (Momoi et al, 2008) and also promotes long-lasting behavioral changes in mouse offspring (Björklund et al, 2008). Nicotine exposure during pregnancy has also been related to a variety of harmful effects, including, among many others, intrauterine growth retardation (Einarson and Riordan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, it was also suggested that caffeine intake should be restricted up to 300 mg/day after quantification studies in a large food sample and after clinical trials with humans and animals performed [3]. Currently, some research groups suggested that the maximum intake should be 100 mg/day or less [9,37,38]. However, a consensus among the maximum caffeine intake has not been established up to now.…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, caffeine as a nonselective adenosine antagonist is expected to influence cardiovascular system. Cardiovascular embryonic function has been assessed by the use of noninvasive high-resolution echocardiography in embryonic mice exposed to caffeine via subcutaneous maternal intake (Momoi et al 2008). The results have shown transient reduced flows in embryonic carotid artery, dorsal aorta and umbilical artery during the highest caffeine concentration in maternal serum.…”
Section: Cardiovascular Systemmentioning
confidence: 99%